2014
DOI: 10.1177/1938640014532131
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the Dorsal Thermoplastic Locking Orthosis to Prevent Floating Toes in Postoperative Follow-up of Weil Osteotomies

Abstract: Therapeutic Level IV: Case Series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…10 In open procedures like a Weil osteotomy, complications like a floating toe can occur in up to 36% of postoperative follow-up. 9 In our series of DMMO, the complication rate was significantly lower.…”
Section: Discussionmentioning
confidence: 53%
“…10 In open procedures like a Weil osteotomy, complications like a floating toe can occur in up to 36% of postoperative follow-up. 9 In our series of DMMO, the complication rate was significantly lower.…”
Section: Discussionmentioning
confidence: 53%
“…According to Godoy‐Santos et al . 24 the Weil osteotomy is considered the principal surgical intervention for the treatment of floating toes. There is a general consensus among foot and ankle surgeons that the downward displacement of the rotation center of the MTP joint, which occurs during surgery, plays a crucial role in the pathogenesis of floating toes.…”
Section: Resultsmentioning
confidence: 99%
“…According to Godoy‐Santos et al 24 . the Weil osteotomy is considered the principal surgical intervention for the treatment of floating toes.…”
Section: Resultsmentioning
confidence: 99%
“…13,14 Our own results resemble the 36% rate that Godoy et al described in their cohort in 2014. 15 In a very well executed comparative study, Henry et al 1 found the amount of persistent pain in patients with either Weil osteotomy or DMMO to be relatively the same (13% and 14%). Our patients experienced persistent pain in 37%.…”
Section: Discussionmentioning
confidence: 99%